Colocalization of tracks from boron neutron capture reactions and images of isolated cells. (January 2021) - Postuma, Ian; Sommi, Patrizia; Vitali, Agostina; Shu, Diyun; Martino, Greta di; Cansolino, Laura; Ferrari, Cinzia; Ricci, Vittorio; Magni, Chiara; Protti, Nicoletta; Fatemi, Setareh; Tamburini, Umberto Anselmi; et al.
Abstract: In Boron Neutron Capture Therapy, the boronated drug plays a leading role in delivering a lethal dose to the tumour. The effectiveness depends on the boron macroscopic concentration and on its distribution at sub-cellular level. This work shows a way to colocalize alpha particles and lithium ions tracks with cells. A neutron autoradiography technique is used, which combines images of cells with images of tracks produced in a solid-state nuclear track detector. Highlights: Overlay of tracks from the 10 B (n, α) 7 Li reaction over cells. An affordable technique to study newly formulated 10 B drugs. Cells can be seeded directly on a CR39. High resolution autoradiography limited by track diameter of ≈ 1 μm.